(untitled) (Baghdad Science Journal, 2007)
The optimum cultural conditions for garamicidin production by local isolate B.brevis were studied.Best result was obtained when the isolate B.brevis was grown on media composed of 1%glucose as carbon source,1% ammonium chloride as a nitrogen source ,0.5% Dipotassium hydrogen orthophosphate as a phosphate source and after 48 hours of incubation at 30C .Garamicidin has been extracted and purified through acid precipition and then extracted by organic solvent (ether& acetone ).Using HPLC the garamicidin antibiotic showed three types A,B and C garamicidin .